2015
DOI: 10.1007/s12070-015-0846-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Large Tympanic Membrane Perforations: Medial to Malleus Versus Lateral to Malleus

Abstract: The perforation size affects the success of tympanic membrane (TM) reconstruction, in addition to the surgical technique used. Large TM perforations present a surgical challenge. The perforation size has been reported to be a prognostic factor, and poorer results are obtained with large versus small perforations. We aimed to evaluate patients who had undergone tympanoplasty for large perforations at our clinic using either the underlay or overunderlay technique and to compare the results in terms of re-perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…These perforations are at high risk of re-perforation, retraction pockets, revision surgeries and are more difficult to treat due to less extensive tympanic membrane margins to support graft survival and less tension to resist tympanic retraction postoperatively. 17 Dangol et al 2 found the graft uptake 83.7% in dry ear, 81.2% in quiescent ear and 75% in actively discharging ear although the result was statistically not significant. The persistent discharge may lead to the displacement of graft, infection of graft material resulting in failure.…”
Section: Discussionmentioning
confidence: 94%
“…These perforations are at high risk of re-perforation, retraction pockets, revision surgeries and are more difficult to treat due to less extensive tympanic membrane margins to support graft survival and less tension to resist tympanic retraction postoperatively. 17 Dangol et al 2 found the graft uptake 83.7% in dry ear, 81.2% in quiescent ear and 75% in actively discharging ear although the result was statistically not significant. The persistent discharge may lead to the displacement of graft, infection of graft material resulting in failure.…”
Section: Discussionmentioning
confidence: 94%
“…The underlay technique positions the graft medial to the tympanic membrane remnant and to the handle of the malleus. It thought to be more suited to posterior perforation and technically easier to perform [9]. The overlay technique is thought to be more suitable for anterior and subtotal perforations, but technically challenging [10].…”
Section: Discussionmentioning
confidence: 99%
“…The over-underlay tympanoplasty technique was introduced as a means of incorporating the advantages of both overlay and underlay techniques, whilst avoiding the disadvantages. 12 It is relatively simple and straightforward, with a good success rate. 1 The handle of the malleus remains an asset in this technique and prevents atelectasis.…”
Section: Discussionmentioning
confidence: 99%